A multi-centre randomised controlled trial of respiratory function monitoring during stabilisation of very preterm infants at birth. (October 2021) - van Zanten, Henriëtte A.; Kuypers, Kristel L.A.M.; van Zwet, Erik W; van Vonderen, Jeroen J.; Kamlin, C. Omar F.; Springer, Laila; Lista, Gianluca; Cavigioli, Francesco; Vento, Maximo; Núñez-Ramiro, Antonio; Oberthuer, Andre; Kribs, Angela; et al.
Abstract: Aim: To determine whether the use of a respiratory function monitor (RFM) during PPV of extremely preterm infants at birth, compared with no RFM, leads to an increase in percentage of inflations with an expiratory tidal volume (Vte) within a predefined target range. Methods: Unmasked, randomised clinical trial conducted October 2013 - May 2019 in 7 neonatal intensive care units in 6 countries. Very preterm infants (24–27 weeks of gestation) receiving PPV at birth were randomised to have a RFM screen visible or not. The primary outcome was the median proportion of inflations during manual PPV (face mask or intubated) within the target range (Vte 4–8 mL/kg). There were 42 other prespecified monitor measurements and clinical outcomes. Results: Among 288 infants randomised (median (IQR) gestational age 26 +2 (25 +3 –27 +1 ) weeks), a total number of 51, 352 inflations were analysed. The median (IQR) percentage of inflations within the target range in the RFM visible group was 30.0 (18.0–42.2)% vs 30.2 (14.8–43.1)% in the RFM non-visible group (p = 0.721). There were no differences in other respiratory function measurements, oxygen saturation, heart rate or FiO2 . There were no differences in clinical outcomes, except for the incidence of intraventricular haemorrhage (all grades) and/or cystic periventricular leukomalacia (visible RFM: 26.7% vs non-visible RFM: 39.0%; RR 0.71 (0.68–0.97); p = 0.028). Conclusion: In very preterm infants receiving PPV at birth, the use of a RFM, compared to no RFM as guidance for tidal volume delivery, did not increase the percentage of inflations in a predefined target range. Trial registration: Dutch Trial Register NTR4104, clinicaltrials.gov NCT03256578.